Minor Parotidectomy Complications: A Systematic Review. (17th July 2020) - Lambiel, Silvia; Dulguerov, Nicolas; Courvoisier, Delphine S.; Dulguerov, Pavel
Abstract : Objectives: To report descriptive statistics for minor parotidectomy complications. Methods: A systematic review was performed, selecting 235 studies for analysis. The incidence of complications was tabulated, and descriptive statistics calculated. Outlier studies, 1 standard deviation above the mean, were reexamined to determine potential causal factors for each complication. All studies were examined for statistically significant differences for any potential causal factor. Results: The pooled incidence of minor complications reported were hematoma 2.9% (95% confidence interval [CI]: 2.4‐3.5), wound infection 2.3% (95% CI: 1.8‐2.9), sialocele 4.5% (95% CI: 3.5‐5.7), salivary fistula 3.1% (95% CI: 2.6‐3.7), flap necrosis 1.7% (95% CI: 1.1‐2.5), scar issues 3.6% (95% CI: 2.4‐5.4), numbness 33.9% (95% CI: 25.6‐43.4), and deformity 11.8 (95% CI: 6.9‐19.5). Implants result in more wound complications, such as hematoma, sialocele, or salivary fistula. Sialocele and salivary fistula appear more frequently after less extensive parotid surgery, whereas hematoma, wound infections, flap necrosis, and aesthetic considerations are worse with more extensive resections. Conclusions: Minor parotidectomy complications are more frequent than generally assumed and related to certain factors that should be investigated. Laryngoscope, 131:571–579, 2021